2019
DOI: 10.3390/ijerph16152800
|View full text |Cite
|
Sign up to set email alerts
|

Dose Tapering Strategy for Heroin Abstinence among Methadone Maintenance Treatment Participants: Evidence from A Retrospective Study in Guangdong, China

Abstract: Around half of methadone maintenance treatment (MMT) participants choose the tapering phase, however, the guidelines on tapering differ between countries and only include the tapering rate. Physicians need more evidence to guide clinical practice. We aimed to explore a specific tapering strategy to improve heroin abstinence among MMT participants. We conducted a retrospective study from 2006 to 2017 at nine MMT clinics in Guangdong, China, involving 853 participants with 961 treatment episodes. We performed tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…However, almost every participant expressed a desire for dose tapering and took action toward full recovery from opioid dependency. This is consistent with previous studies, which indicated that around 41–57% of participants tapered their doses [ 28 , 29 ]. According to our findings, the frequency, speed, and duration of dose tapering varied among participants, with those on relatively higher doses, such as over 100 mg per day, being more adaptable to larger decreases.…”
Section: Discussionsupporting
confidence: 93%
“…However, almost every participant expressed a desire for dose tapering and took action toward full recovery from opioid dependency. This is consistent with previous studies, which indicated that around 41–57% of participants tapered their doses [ 28 , 29 ]. According to our findings, the frequency, speed, and duration of dose tapering varied among participants, with those on relatively higher doses, such as over 100 mg per day, being more adaptable to larger decreases.…”
Section: Discussionsupporting
confidence: 93%
“…Drop-out was usually defined as being absent from MMT for more than 14 consecutive days ( 39 ). The continuous treatment days were days participants resumed MMT after their last drop-out ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Drop-out was usually de ned as being absent for MMT for more than 14 consecutive days 30 . The continuous treatment days were days participants resumed MMT after their last drop-out 19 .…”
Section: Continuous Treatment Daysmentioning
confidence: 99%